Comparison of Hematopoietic Stem Cell Transplantation Outcomes Using Matched Sibling Donors, Haploidentical Donors, and Immunosuppressive Therapy for Patients With Acquired Aplastic Anemia - Zhang, Yuanfeng; Huo, Jiali; Liu, Li; Shen, Yuyan; Chen, Juan; Zhang, Tingting; Chen, Xin; Pang, Aiming; Yang, Donglin; Zhang, Rongli; Ma, Qiaoling; Zhai, Weihua; et al. (Frontiers in Immunology, 2022)
We retrospectively compared the outcomes of 387 consecutive patients with acquired aplastic anemia (AA) who underwent hematopoietic stem cell transplantation (HSCT) with a fludarabine-based conditioning regimen from matched sibling donors (MSD) (n=108) or haploidentical donors (HID) (n=91) and immunosuppressive therapy (IST) (n=188) from 2014 to 2020 at our hospital. Compared with HID-HSCT, MSD-HSCT had a lower incidence of graft failure (1% vs. 7%, P=0.062), grade II-IV acute graft versus host disease (aGvHD) (16% vs. 35%, P=0.001), and mild to severe chronic GvHD (cGvHD) (8% vs. 23%, P=0.007), but an equivalent incidence of grade III-IV aGvHD (8% vs. 12%, P=0.237) and moderate to severe cGvHD (3% vs. 9%, P=0.076). HSCT had superior blood count recovery at 3, 6, and 12 months compared with IST (P<0.001). The estimated 5-year overall survival (OS) of the MSD, HID, and IST groups were 86%, 72%, and 79% (P=0.02), respectively; accordingly, the failure-free survival (FFS) rates were 85%, 68%, and 56%, respectively (P<0.001). For patients aged≤40 years, the OS were comparable between the HID and MSD-HSCT recipients (89% vs. 79%, P=0.2) while the HID-HSCT recipients showed similar OS (79% vs. 78%, P=0.242) but superior FFS (P=0.047) when follow-up was longer than 14.5 months in contrast to IST. In a multivariate analysis, HID-HSCT and a conditioning regimen that included busulfan were adversely related to OS among patients who received allografts. In conclusion, MSD-HSCT was the frontline choice for patients with severe AA aged≤40 years, while HID-HSCT was as effective as IST for patients without an MSD.